2022
DOI: 10.31083/j.fbl2712332
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Hen Eggs Enriched with n-3 Polyunsaturated Fatty Acids, Selenium, Vitamin E and Lutein Incites Anti-Inflammatory Conditions in Young, Healthy Participants — A Randomized Study

Abstract: Background: Dietary supplementation with compounds that possess antioxidant and anti-inflammatory properties (n-3 polyunsaturated fatty acids (PUFAs), selenium, vitamin E, lutein), has been shown to positively correlate with improvements in chronic conditions, although understanding of these combined effects in healthy humans is limited. The study aimed to evaluate the effects of enriched eggs consumption on oxidative status and inflammatory conditions in healthy volunteers. We hypothesized that a three-week d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…This finding aligns with a separate study involving young healthy participants, which also reported a significant increase in serum vitamin E concentration after consuming eggs enriched with n-3 PUFA, vitamin E, selenium, and lutein. 34 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding aligns with a separate study involving young healthy participants, which also reported a significant increase in serum vitamin E concentration after consuming eggs enriched with n-3 PUFA, vitamin E, selenium, and lutein. 34 …”
Section: Discussionmentioning
confidence: 99%
“… 55 , 56 A significant increase in serum selenium concentration was observed in the Nutri4 group, consistent with similar results reported in previous research. 34 The synergistic effect of vitamin E and selenium in eliminating lipid peroxides, formed as a result of excessive ROS interaction with PUFA, is well-known. Vitamin E acts directly as an antioxidant, while selenium serves as a cofactor for GPx enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They serve as a high quality complementary food for infants and play a crucial role in brain and immune development [2,3]. In recent years, there has been a growing interest among consumers in functional eggs, which possess the ability to lower blood lipids [4], reduce inflammation [5], and enhance immunity [6].…”
Section: Introductionmentioning
confidence: 99%